Validação da escala Pain Quality Assessment Scale (PQAS) para o português do Brasil - CARVALHO , Anamada Barros (2019)
Introduction: The diagnosis of Chemotherapy-Induced Peripheral Neuropathy (NPIQ) is a challenge for health professionals who attend cancer patients. The PQAS is an instrument of self-report used in clinical practice to assess the quality of pain, evaluating the patient's perception about your treatment or medical condition Objective: Validation of the Pain Quality Assessment Scale (PQAS) into Portuguese of Brazil. Methods: From a convenience sample were selected 140 cancer patients and applied the questionnaires PQAS and DN4 (Douleur Neuropathique 4 Questionnaire). The last step was to apply the following psychometric properties for validation: concurrent validity by Spearman’s correlation test compared to the DN4 questionnaire; construct validity by construct validity by the confirmatory factorial analysis (CFA) and after the test was the reliability of the Cronbach's Alpha coefficient. Results: In the concurrent validity study, the values of the coefficient ρ Spearman Correlation showed a moderate correlation between the scores of the dimensions of pain (ρ = 0.47), specific quality (ρ = 0.68) and spatial quality of pain (ρ = 0.53) of the PQAS with the DN4 scale, with significance levels below 0.05; in the CFA qualities with burning, tingling and radiating was smaller factorial loads. Regarding reliability, it was reached a Cronbach's alpha of 0.91, satisfactory. Conclusion: PQAS is a valid and reliable scale, can be used as an important tool for evaluation of neuropathic pain after chemotherapy in Brazil.